(untitled) - Horowitz, Anthony; 1955- (New York, 2004)
After a chance encounter with assassin Yassen Gregorovich in the South of France, teenage spy Alex Rider investigates international pop star and philanthropist Damian Cray whose new video game venture hides sinister motives involving Air Force One, nuclear missiles, and the international drug trade.
Keywords: Fiction; Fiction; Orphans; Fiction; Spies; Adventure and adventurers; Camargue (France); Fiction; France; Fiction